New insights on employee adaptive performance during the COVID-19 pandemic: Empirical evidence from Indonesia - Ronny Tan; Ferdi Antonio (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: This study investigates how perceived e-leadership and the teleworking output are linked to employee adaptive performance. Further, it seeks to comprehend whether a sense of purpose and organizational commitment have a mediating role. This study proposes a new research model that is empirically tested to predict employee adaptive performance, especially during remote working due to the COVID-19 pandemic. METHODOLOGY: A quantitative survey was conducted in August 2021. Respondents were obtained from 271 teleworkers employed in a reputable private company operating in the financial industry in Indonesia. The data was collected by a questionnaire using a Likert-type scale and then analyzed using PLS-SEM. FINDINGS: Three antecedents are proven to affect employee adaptive performance directly: organizational commitment, followed by teleworking output, and a sense of purpose. Perceived e-leadership affects employee adaptive performance indirectly, and it is mediated through teleworking output, organizational commitment, and sense of purpose. IMPLICATIONS: This insight suggests that management must take care of intrinsic motivation to get the employees performing in the organization. These constructs will play significant roles and, therefore, should be well-planned, well-executed, and seriously measured to strengthen employee adaptive performance in an organization. The research model result shows moderate predictive accuracy strength with medium predictive relevance on employee adaptive performance, giving opportunities to re-use and extend the research model and explore other constructs. Based on the findings, management needs to focus on trust in employees, team motivation, and employee-experience management activities to keep the employees engaged. ORIGINALITY AND VALUE: This is one of the first studies to deploy intrinsic motivation as an antecedent of employee adaptive performance, together with the perceived e-leadership and teleworking output. Corporations will be able to focus on some key areas that are proven to impact employee adaptive performance positively.